A virtual cage for monitoring system semi-intensive livestock's using wireless sensor network and Haversine method - Fahmi Danah Pratama; Giva Andriana Mutiara; Lisda Meisaroh (JURNAL INFOTEL, 2023)
Indonesia has great livestock potential. The semi-intensive grazing system is one of the efforts to increase the production of healthy and superior dairy or beef livestock. This grazing system has many advantages. However, it has several weaknesses that can prejudice farmers, including lost or stolen livestock due to a lack of control and monitoring. Therefore, tracking livestock's position in the WSN-based grasslands monitoring will be implemented to overcome these weaknesses. Thus, it will provide benefits as a support for a modern and controlled livestock system. The built WSN consists of several nodes installed on livestock consisting of Arduino nano, GPS Neo Module, LoRa S-1278, DS3231 clock module, and MCU node. Tracking is visible through the application by displaying the map and livestock's GPS position. In addition, the system is notified if the livestock's position is located more than in the permitted radius of the farm. The system was examined and analyzed using the Haversine method with various scenarios to find the maximum range transmission and perform system toughness. The results stated that the system could track the livestock's position up to 11 Km and the location error calculation obtained by Haversine is only 11.7% of the actual location.